Jak rozumieć godność w prawie - Najman, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In the current legal discourse, the concept of dignity is becoming more common. It is considered the highest axiom, whose every violation deserves to be condemned. However, we forget about the conceptual basis of a given concept, its history, and original overtones. We do not remember that certain concepts are created solely to systematize the created or existing social and political situations. The purpose of the article is an attempt to answer the question of how to understand the concept of dignity in legal discourse. It is worth bearing in mind that dignity is indicated as “this” (value or maybe something else) from which human rights originate. That is why it should be rejected as a value because the value itself is not a value. However, one must opt for an objective understanding of dignity, rejecting its moral background proposed, among others by the doctrine of the Catholic Church, if we want to treat it as a legal category.
Keywords: dignity; value; legal category